The Persian Cinderella - Shirley Climo (New York HarperCollins Children's Books, 2001)
In this jewel-like version of a classic story, popular folklorist Shirley Climo tells the tale of Settareh, the Persian Cinderella. Magic enables Settareh to outsmart two jealous stepsisters and win the heart of a prince. But where most Cinderella stories end, poor Sattareh's troubles are only beginning! The unexpected plot twists will enchant readers as they rediscover the familiar tale in the lush setting of long-ago Persia. Shirley Climo's authentic details bring the story to life, and Robert Florczak's stunning paintings echo the vibrant colors and motifs of an ancient land. 01-02 TX Bluebonnet Award Masterlist
Keywords: Anthology Fantasy -- PY-UOI-Who We Are; Circle Time Book - Traditional Literature & Fairytales/ Folklore Myths & Legends / Fables -- Circle Time Book - Traditional Literature & Fairytales/ Folklore Myths & Legends / Fables